Elevated Creatinine Kinase in Peripheral Neuropathy Is Associated With Muscle Cramping - Jordan, Allison; Nagaraj, Arun; Hoyle, J. Chad; Stino, Amro Maher; Arnold, W. David; Elsheikh, Bakri (Frontiers in Neurology, 2021)
Introduction: Serum Creatinine Kinase (CK) is a non-specific marker of muscle damage. There has been limited investigation of the association between peripheral neuropathy and CK elevation (hyperCKemia). Methods: We performed a chart review to investigate the CK level in peripheral neuropathies. Demographics, clinical history, physical exam, electrodiagnostic data, CK level, statin use, etiology of neuropathy, and concomitant neuromuscular disorders were recorded. HyperCKemia was defined using our laboratory cutoff values of >180 U/L (women) and >220 U/L (men). Results: We identified 450 patients with peripheral neuropathy who had CK testing, 92 (20.4%) of whom had hyperCKemia. Sixty-one of those patients (13.5% of the total figure) had a concomitant etiology that could explain the CK elevation. Thirty-one patients (6.9%) had no other identifiable etiology for their hyperCKemia beyond the neuropathy. The average CK level in the latter cohort with hyperCKemia was 376 U/L (women: 312 U/L; men: 444 U/L). The frequency of cramping was greater in patients with elevated vs. normal CK (p < 0.0001). Discussion: HyperCKemia can occur in patients with peripheral neuropathy and appears to associate with cramping.